Pemberdayaan Santri Melalui Inovasi Digitalisasi & Promosi Food Heritage: Pelestarian Makanan Tempoyak Khas Daerah Jambi di Pondok Pesantren Nurul Furqon Tebo Jambi - Umi Rossy Mardhiyah; Maulana Apriliansah; Navakhatus Sa'diyah; Nazilatun Nikmah; M. Nur Kholis Mujib (Journal of Innovation and Contribution to Community Service, 2026)
Tempoyak is a traditional food made from durian fruit, scientifically known as Durio zibethinus, which is a plant that grows exclusively in tropical regions. One of the major durian-producing areas in Indonesia is Jambi Province on the island of Sumatra. This study aims to provide education for Islamic boarding school students on science and technology through efforts to preserve local traditional foods, specifically tempoyak, in order to prevent them from becoming extinct or forgotten amid the increasing popularity of contemporary foods. The method used in this activity is Participatory Action Research (PAR). The implementation of the PAR method consists of three stages: preparation, implementation, and evaluation. This activity aims to enhance students’ environmental awareness as well as their understanding of the importance of preserving local food culture within the Nurul Furqon Islamic Boarding School, located in Perintis Village, Rimbo Bujang District, Tebo Regency, Jambi Province. The results of this activity provide various benefits, not only for the internal community of the Islamic boarding school but also for the wider community, as the program is productive, educational, and creative. Furthermore, this activity is expected to improve the quality of students’ life skills, which can be further developed and utilized in a sustainable manner.